Reboisasi dan Rehabilitasi Lahan di Bukit Lambosir Kawasan Taman Nasional Gunung Ciremai Bersama Kelompok Masyarakat Ciremai Green Lambosir - Sulistyono Sulistyono; Sofyan H. Nur; Zamzam Saeful Anwar; Deden Ramdhan Hadi (Empowerment : Jurnal Pengabdian Masyarakat, 2025)
Forest degradation and land conversion threaten the ecological functions of conservation areas. Mount Ciremai National Park (TNGC) in West Java faces increasing pressures from local activities and unregulated tourism. The “Forest and Land Rehabilitation” is a community-based conservation service program involving the Ciremai Green Lambosir community group (Kompepar). The program aimed to enhance human resource capacity, conduct reforestation using endemic vegetation, provide ecotourism interpretation facilities, and promote conservation-based tourism. The implementation methods included training, participatory discussions, planting endemic trees, installing interpretation boards, and promoting the site through social media. The results show increased Kompepar members’ capacity in tourism interpretation, identification and planting of 11 native vegetation species, and greater community engagement in reforestation. The program provided ecological benefits through improved vegetation cover, social benefits through strengthened community institutions, and economic benefits through ecotourism promotion.